Nursing assessment: Research/Care through the sensible listening in the heart failure clinic. - Liana Amorim Corrêa; Iraci dos Santos; Denilson Campos de Albuquerque (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Assuming that nursing assessment for heart failure clients help us to face the changes in your daily, we enquire what the contribution of sensible listening applied to nursing assessment. The purpose is to identify the needs of care creating a new way to care/research sensibly through nursing appointment. The methodology of quantitative character and exploratory applied in the form of evaluation was performed by 50 clients in an hospital in Rio de Janeiro. It was found that 100% of the people have lack of knowledge about HF, followed by diet and medicines. Analyzing social field, there is a majority of 38% with no commitment to treatment, 36% with poor economic conditions and 32% related to bad nutrition. Nursing interventions were applied to solve problems identified beyond medicative therapy, allowing the client to have an exclusive treatment extended to its mental/intellectual and spiritual dimensions.